2018
DOI: 10.1111/jdi.12894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of insulin glargine 300 U/mL and insulin degludec using flash glucose monitoring: A randomized cross‐over study

Abstract: The two formulations were comparable in efficacy, whereas the incidence of nocturnal hypoglycemia was significantly lower with Gla300. Thus, the present study suggests that, although Gla300 and Deg are comparable long-acting insulin analogs, Gla300 is safer with respect to the incidence of hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 29 publications
0
48
0
2
Order By: Relevance
“…A second head-to-head study conducted in adults with T2D already receiving insulin did not demonstrate superiority for IDeg-100 versus Gla-300 during the maintenance period [16]. To our knowledge, two small studies have been published that compare Gla-300 and IDeg-100 in people with T2D using CGM, both conducted in Japan [17,18]. Yamabe et al reported no statistically significant difference between the two insulins in any of the CGM metrics assessed, including mean TIR, mean time below range (TBR; both \ 70 and \ 54 mg/dL) and mean coefficient of variation (CV; a CV of \ 36% is taken to represent stable glycaemia [18,19].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A second head-to-head study conducted in adults with T2D already receiving insulin did not demonstrate superiority for IDeg-100 versus Gla-300 during the maintenance period [16]. To our knowledge, two small studies have been published that compare Gla-300 and IDeg-100 in people with T2D using CGM, both conducted in Japan [17,18]. Yamabe et al reported no statistically significant difference between the two insulins in any of the CGM metrics assessed, including mean TIR, mean time below range (TBR; both \ 70 and \ 54 mg/dL) and mean coefficient of variation (CV; a CV of \ 36% is taken to represent stable glycaemia [18,19].…”
Section: Introductionmentioning
confidence: 92%
“…To our knowledge, two small studies have been published that compare Gla-300 and IDeg-100 in people with T2D using CGM, both conducted in Japan [17,18]. Yamabe et al reported no statistically significant difference between the two insulins in any of the CGM metrics assessed, including mean TIR, mean time below range (TBR; both \ 70 and \ 54 mg/dL) and mean coefficient of variation (CV; a CV of \ 36% is taken to represent stable glycaemia [18,19]. However, Kawaguchi et al observed significantly lower anytime (24 h) and nocturnal (0000-0600 hours) CV and TBR with Gla-300 than with IDeg-100 [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the BRIGHT trial, event rates of anytime and nocturnal confirmed hypoglycemia were lower with IGla-300 than with IDeg during the initial titration period (0-12 weeks) [23]. Recently, Yamabe et al also reported that the incidence of nocturnal hypoglycemia, of which patients might be unaware, with IGla-300 (n = 24) was significantly lower than that with IDeg (n = 24) in crossover study using a flush glucose monitoring (FGM) system [27]. The low-level hypogly-cemia might have been overlooked in our study because of lacking daily glucose profile by FGM or continuous glucose monitoring, we might underestimate the frequency of hypoglycemia unawareness but did not observe any serious episodes of hypoglycemia throughout the observation.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it was reported that Gla-300 has lower possibility of hypoglycaemia than Gla-100 and insulin degrudec [43][44][45][46] . The peak of Gla-300 was reported to be lower than Gla-100 and presented 12-13 h later 46 .…”
Section: Discussionmentioning
confidence: 99%